A Peer-To-Peer Publication Model on Blockchain - Khan, Imtiaz; Shahaab, Ali (Frontiers in Blockchain, 2021)
In the past few decades there has been a sharp rise of research irreproducibility and retraction, to a point that now is deemed as crisis. Addressing this crisis, we present a peer-to-peer (P2P) publication model that utilizes blockchain and smart contract technologies. Focusing primarily on researchers and reviewers, the conceptual P2P publication model addresses the sociocultural and incentivization aspects of the irreproducibility crisis. In the P2P publication model, instead of a complete publication, a preapproved experimental design will be published on incremental basis (unit-by-unit) and authorship will be shared with reviewers. The concept of P2P publication model was inspired by the transformational journey the music publishing industry has undertaken as it traverses through vinyl age (complete albums) to the Spotify age (single-by-single), where there is a growing inclination among artists towards building an incremental album, taking account of feedback from fans and utilizing automated revenue collection and sharing systems. The ability to publish incrementally through P2P publication model will relieve researchers from the burden of publishing complete and “good results” while simultaneously incentivizing reviewers to undertake rigorous review work to gain authorship credit in the research. The proposed P2P publication model aims to transform the century old publication model and incentivization structure in alignment with open access publication ethos of the twenty first century.